Volume 99A, Number 9, September 2021 Cover Image. Issue 9 (1st September 2021) - Unknown
Abstract: This month's issue looks back at the optimized multicolor immunophenotyping panels (OMIPs) that have been published in Cytometry Part A over the past decade. Read more about this significant body of work in this issue's editorial and Wang and Creusot's review https://doi.org/10.1002/cyto.a.24471 .